Optimisation of alendronate conjugation to polyethylene glycol for functionalisation of biopolymers and nanoparticles. (15th July 2021) - Poli, Hamish; Mushtaq, Asim; Bell, Craig A.; McGeary, Ross P.; Grøndahl, Lisbeth; A, Anitha
Graphical abstract: Synthesis, isolation and characterisation of alendronate ALN-PEG-NH2, ALN-PEG-COOH and ALN-PEG-Chitosan achieved using optimised reaction conditions between alendronate. and 2-iminothiolane. Highlights: Orthogonal synthesis and characterisation of isolated alendronate-PEG-chitosan. Alendronate-PEG is chemically stable up to at least 1 week in vitro. Mechanistic insight into reaction of the high pKa amine alendronate with 2-iminothiolane revealing pH and time dependence. High pKa amine derived iminothiolane adducts don't restore thiol upon acidification. Abstract: The coupling of alendronate (ALN) to heterobifunctional polyethylene glycol (PEG) requires an orthogonal synthetic route. This can be achieved using thiolation of alendronate with 2-iminothiolane and subsequent Michael addition to maleimide functionalised PEG. This paper evaluates the chemical reactions between 2-iminothiolane and alendronate and demonstrates how reaction conditions previously reported for thiolation of amines are not ideal in reactions where the amine has a high p K a value, such as for amine-containing bisphosphonates. Furthermore, the optimised method for thiolation of alendronate is applied to the synthesis of alendronate functionalized PEGs, ALN-PEG-NH2 and ALN-PEG-COOH, with isolation and full characterization of these two products. Further conjugation of the latter onto the biopolymer chitosan is demonstrated, including evaluating reagent ratios on the degree of substitution.